The influence of perceived security and user mobility toward intention to use mobile payment Shopeepay with perceived usefulness as mediating variable - Afif Muhammad Adventure; Yunita Engriani (Universitas Negeri Padang, 2022)
This study aims to analyze (1) the effect of perceived security on intention to use on student mobile payment Shopeepay users mediated by perceived usefulness in the city of Padang. (2) The effect of user mobility on the intention to use of mobile payment users in Shopeepay students is mediated by perceived usefulness in the city of Padang. The population used in the study were students using Shopeepay mobile payment users and the sample used was students using Shopeepay mobile payment users in the city of Padang for at least 1 use. The number of samples in this study was 159 total respondents. Data was collected through online questionnaires and data processing using PLS (Partial Least Square) software. The results of this study indicate that. (1) Perceived security has a positive and significant effect on the intention to use Shopeepay's mobile payment. (2) User mobility has a positive and significant effect on the intention to use Shopeepay's mobile payment. (3) Perceived usefulness has a positive and significant effect on the intention to use Shopeepay's mobile payment. (4) Perceived security has a positive and significant effect on the perceived usefulness of students using Shopeepay mobile payment users in the city of Padang. (5) User mobility has a positive and significant effect on the perceived usefulness of Shopeepay mobile payment users in the city of Padang (6) Perceived security has a positive and significant effect on the intention to use Shopeepay's mobile payment mediated by perceived usefulness. (7) User mobility has a positive and significant effect on the intention to use Shopeepay's mobile payment mediated by perceived usefulness.